Progression of Luminal Breast Tumors Is Promoted by Ménage à Trois between the Inflammatory Cytokine TNFα and the Hormonal and Growth-Supporting Arms of the Tumor Microenvironment - Weitzenfeld, Polina; Meron, Nurit; Leibovich-Rivkin, Tal; Meshel, Tsipi; Ben-Baruch, Adit (Mediators of Inflammation, 2013)
Breast cancer progression is strongly linked to inflammatory processes, aggravating disease course. The impacts of the inflammatory cytokine TNFα on breast malignancy are not fully substantiated, and they may be affected by cooperativity between TNFα and other protumoral mediators. Here, we show that together with representatives of other important arms of the tumor microenvironment, estrogen (hormonal) and EGF (growth-supporting), TNFα potently induced metastasis-related properties and functions in luminal breast tumor cells, representing the most common type of breast cancer. Jointly, TNFα + Estrogen + EGF had a stronger effect on breast cancer cells than each element alone, leading to the following: (1) extensive cell spreading and formation of FAK/paxillin-enriched cellular protrusions; (2) elevated proportion of tumor cells coexpressing high levels of CD44 and β1 and VLA6; (3) EMT and cell migration; (4) resistance to chemotherapy; (5) release of protumoral factors (CXCL8, CCL2, MMPs). Importantly, the tumor cells used in this study are known to be nonmetastatic under all conditions; nevertheless, they have acquired high metastasizing abilities in vivo in mice, following a brief stimulation by TNFα + Estrogen + EGF. These dramatic findings indicate that TNFα can turn into a strong prometastatic factor, suggesting a paradigm shift in which clinically approved inhibitors of TNFα would be applied in breast cancer therapy.